Occupational choice, human capital, and financial constraints - Rui Castro; Pavel Ševčík (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2016)
We study the aggregate productivity effects of firm-level financial frictions. Credit constraints affect not only production decisions but also household-level schooling decisions. In turn, entrepreneurial schooling decisions impact firm-level productivities, whose cross-sectional distribution becomes endogenous. In anticipation of future constraints, entrepreneurs under-invest in schooling. Frictions lower aggregate productivity because talent is misallocated across occupations, and capital misallocated across firms. In addition, firm-level productivities are also lower due to distortions induced by the schooling responses. We find that these effects combined account for about 1/5 of the U.S.-India aggregate productivity difference. Requiring the model to match schooling differences significantly amplifies the impact of frictions, and the model accounts for 58% of the aggregate productivity difference.
Keywords: E24; I25; J24; O11; O15; O16; O47; 330; Aggregate Productivity; Financial Frictions; Entrepreneurship; Human Capital